Corporate brand strategy formation: Brand actors and the situational context for a business-to-business brand - Vallaster, Christine; Lindgreen, Adam (Industrial marketing management, 2011)
Prior literature on corporate branding in the business-to-business (B2B) context fails to provide insight into the dynamics of corporate brand strategy formation, despite the critical need for industrial organizations to move beyond a traditional understanding of brands. This article examines the corporate brand strategy formation of a European-based industrial organization by drawing on strategy-as-practice research and thereby identifying the brand actors who participate in corporate brand strategy formation, the construction of manifestations that subject the brand values to experience, and the situational context—all within a single, ongoing, recursive interaction process.